2009
DOI: 10.2967/jnumed.109.063016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time-of-Flight on PET Tumor Detection

Abstract: Time-of-flight (TOF) PET uses very fast detectors to improve localization of events along coincidence lines-of-response. This information is then utilized to improve the tomographic reconstruction. This work evaluates the effect of TOF upon an observer's performance for detecting and localizing focal warm lesions in noisy PET images. Methods: An advanced anthropomorphic lesion-detection phantom was scanned 12 times over 3 days on a prototype TOF PET/CT scanner (Siemens Medical Solutions). The phantom was devis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
195
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(211 citation statements)
references
References 22 publications
14
195
1
1
Order By: Relevance
“…The delineated lesion is also shown in green in the figure. Consistent with the previous findings (22)(23)(24)(25)(26), OSEM 1 TOF 1 PSF produced visually the best image among the chosen 4 reconstruction algorithms with their default settings. In addition, quantitative assessment supported the fact that OSEM 1 TOF 1 PSF produced the best image with an SNR of 9.1 in the liver, whereas the SNR of OSEM, OSEM 1 PSF, and OSEM 1 TOF were 5.2, 5.5, and 8.5, respectively.…”
Section: Change Of Image Features Over Default Reconstruction Settingssupporting
confidence: 79%
See 2 more Smart Citations
“…The delineated lesion is also shown in green in the figure. Consistent with the previous findings (22)(23)(24)(25)(26), OSEM 1 TOF 1 PSF produced visually the best image among the chosen 4 reconstruction algorithms with their default settings. In addition, quantitative assessment supported the fact that OSEM 1 TOF 1 PSF produced the best image with an SNR of 9.1 in the liver, whereas the SNR of OSEM, OSEM 1 PSF, and OSEM 1 TOF were 5.2, 5.5, and 8.5, respectively.…”
Section: Change Of Image Features Over Default Reconstruction Settingssupporting
confidence: 79%
“…Thus, the impact of the partial-volume effect can be neglected. Previous studies (22)(23)(24)(25)(26) demonstrated that OSEM 1 PSF 1 TOF produced better image quality than other methods in terms of SNR, contrast, and lesion detectability. Therefore, in this study, the tumor VOIs were delineated on the image reconstructed by OSEM 1 PSF 1 TOF with default settings and then applied to the other methods.…”
Section: Tumor Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of time-of-flight (TOF) information in positron emission tomography (PET) has recently been demonstrated to enable significant improvement in image noise properties and, therefore, lesion detection, especially in heavier patients (Kadrmas et al 2009, Lois et al 2010, Moses 2007, Surti et al 2007. This warrants further research into TOF-capable PET scintillation detectors, in particular with the aim to obtain better timing resolution.…”
Section: Introductionmentioning
confidence: 99%
“…2 in [19], one can estimate the maximum angular interval (α max ) that provides adequate sampling consistent with the spatial resolution of the data as (1) In this calculation, FWHM LOR is defined by the detector spatial resolution rather than the pixel size as was done in [19]. The subsequent minimum number of transverse angular samples (nϕ min ) and tilt angles (nθ min ) can be calculated from (2) (3) where θ max is the full axial angular range of the scanner. For a whole-body TOF-PET scanner with 6-mm resolution and 430-ps timing resolution, only 17 transverse angular samples and 2 oblique tilt angles are required; for a scanner with 700-ps timing resolution, 28 transverse views and 3 oblique tilt angles are needed.…”
Section: Introductionmentioning
confidence: 99%